2017
DOI: 10.1186/s11689-017-9205-x
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder (ADHD) in phenotypically similar neurogenetic conditions: Turner syndrome and the RASopathies

Abstract: BackgroundADHD (attention deficit hyperactivity disorder) is a common neurodevelopmental disorder. There has been extensive clinical and basic research in the field of ADHD over the past 20 years, but the mechanisms underlying ADHD risk are multifactorial, complex and heterogeneous and, as yet, are poorly defined. In this review, we argue that one approach to address this challenge is to study well-defined disorders to provide insights into potential biological pathways that may be involved in idiopathic ADHD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 120 publications
0
25
1
1
Order By: Relevance
“…Research among children diagnosed with NF1 and NS has consistently identified difficulties related to attention problems and social deficits (Adviento et al, ; Green et al, ; Noll et al, ; Pierpont et al, ). Results of the current study emphasize the need for further examination of internalizing symptoms among individuals with RASopathies, especially in children with a comorbid ADHD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Research among children diagnosed with NF1 and NS has consistently identified difficulties related to attention problems and social deficits (Adviento et al, ; Green et al, ; Noll et al, ; Pierpont et al, ). Results of the current study emphasize the need for further examination of internalizing symptoms among individuals with RASopathies, especially in children with a comorbid ADHD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder (ADHD) is associated with a significant proportion of RASopathy cases (Adviento et al, 2014; Garg et al, 2013; Green et al, 2017; Pierpont et al, 2018; Walsh et al, 2013). Altered prefrontal cortex (PFC) function has been implicated in ADHD (Gabay et al, 2018), and has been shown to contribute to cognitive deficits in a mouse model of Fragile X Syndrome (Krueger et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Examples include neurofibromatosis type 1 (NF1), Noonan syndrome, Costello syndrome, cardiofaciocutaneous syndrome, and LEOPARD syndrome (47). Patient phenotypes of the various syndromes are diverse, but share some overlapping features, including cardiac and vascular abnormalities, developmental delay, neurodevelopmental phenotypes (autism and ADHD) and predisposition to cancer (48)(49)(50). Intriguingly, all individuals haploinsufficient for CIC have developmental delay and neurodevelopmental phenotypes, and some individuals have cardiac and vascular abnormalities (5).…”
Section: Discussionmentioning
confidence: 99%